2019
DOI: 10.3390/polym11030456
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Conductivity of Protein-Based Materials: A Review

Abstract: Fibrous proteins such as silks have been used as textile and biomedical materials for decades due to their natural abundance, high flexibility, biocompatibility, and excellent mechanical properties. In addition, they also can avoid many problems related to traditional materials such as toxic chemical residues or brittleness. With the fast development of cutting-edge flexible materials and bioelectronics processing technologies, the market for biocompatible materials with extremely high or low thermal conductiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 46 publications
(32 citation statements)
references
References 125 publications
1
31
0
Order By: Relevance
“…However, no third degradation peak (T d3 ) was observed around 600~700 °C for any of Co-SF samples. The first small degradation is mainly from the unstable part of silk proteins [ 32 , 33 , 34 ]. BaM-SF samples showed a higher T d1 than that of the other two types of composites, suggesting that BaM particles were able to best protect silk materials.…”
Section: Resultsmentioning
confidence: 99%
“…However, no third degradation peak (T d3 ) was observed around 600~700 °C for any of Co-SF samples. The first small degradation is mainly from the unstable part of silk proteins [ 32 , 33 , 34 ]. BaM-SF samples showed a higher T d1 than that of the other two types of composites, suggesting that BaM particles were able to best protect silk materials.…”
Section: Resultsmentioning
confidence: 99%
“…Many biosensors and bioelectronics also require temperature sensors or heat transfer components [22,23]. It was found that the thermal conductivity of silk can be improved by increasing the crystallinity of silk proteins, although it is still much lower than many inorganic materials [24][25][26]. On the other hand, boron nitride (BN) nanomaterials have excellent thermal stability, thermal conductivity, and stable chemical properties, and have long-term good insulation properties [27][28][29][30].…”
Section: Introductionmentioning
confidence: 99%
“…Porosity fraction = 0.67 [32] Porosity fraction = 0.85 [33] Slope = 0.67 for reference Slope = 0.85 for reference Figure 7. Comparison of logarithmic mixing rule with experimental data of (a) packed beds [5,26] (b) rocks [29,30] and (c) high temperature porous ceramics [38,39].…”
Section: (K)]mentioning
confidence: 99%
“…Interest in the thermal characteristics of multi-phase and composite materials has continued to grow, as the need for such materials across a broad spectrum of areas has increased; sectors of interest include aerospace, packaging, electronics, construction and processing [1][2][3][4][5][6][7][8][9]. Composites with high levels of thermal conductivity are attractive for applications related to heat dissipation and heat sinks [10], such as high-power electronics and brake friction linings, and low conductivity composites are necessary for insulation and thermal protection.…”
Section: Introductionmentioning
confidence: 99%